The adsorption of arsenate and p-arsanilic acid onto ferrihydrite and subsequent desorption by sulfate and artificial seawater: Future implications of sea level rise. (15th April 2023) - Barreto, Matheus Sampaio C.; Elzinga, Evert J.; Sparks, Donald L.
Abstract: Sea level rise (SLR) is estimated to impact 25% of the world's population along coastal areas leading to an increase in saltwater intrusion. Consequently, changes in the soil biogeochemistry of currently non-saline and/or well-drained soils due to saltwater intrusion are of major concern. Saltwater intrusion is expected to affect farmland across large broiler producer regions, where large amounts of manure containing organic arsenicals were applied over the past decades. To determine how SLR may impact the speciation and mobility of adsorbed inorganic and organic As, we used in situ real-time attenuated total reflectance–Fourier transform infrared spectroscopy (ATR-FTIR) to determine the adsorption and desorption mechanisms of As(V) and 4-aminophenylarsonic (p-ASA, a poultry feed additive) on ferrihydrite (Fh) in the presence of sulfate at varying pH. The adsorption of As(V) and p-ASA increased at lower pH, with As(V) showing IR features consistent with the formation of inner-sphere of As-Fh surface complexes, while p-ASA also formed others structures as H-bonded As-surface complexes, likely mediated by outer-sphere complexes, based on our FTIR and batch experiments data. No observable As(V) or p-ASA desorption from the Fh surface was promoted by sulfate, however sulfate adsorption on the Fh surface was remarkably larger for p-ASA than for As(V). Complimentary, we carried out batch studies of As(V) and p-ASA desorption by Fh, using artificial seawater (ASW) at varying concentrations. The 1% ASW desorbed ∼10% of initially sorbed p-ASA, while at 100% ASW desorbed ∼40%. However, <1% of As(V) was desorbed by 1% ASW solution and only ∼7.9% were desorbed at 100% ASW. The spectroscopic data support the more extensive desorption of p-ASA compared to As(V) observed in batch experiments, suggesting that organoarsenicals may be easily desorbed and, after conversion to inorganic forms, pose a risk to water supplies. Graphical abstract: Image 1 Highlights: In-situ ATR-FTIR was used to determine the adsorption mechanisms of As-compounds on ferrihydrite. Adsorbed-p-arsanilic presented some features of outer-sphere surface complexation. Artificial seawater desorbed more p-arsanilic than As(V). Desorbed organoarsenicals pose a risk to water quality in sea-level-rise scenarios.